Changes in the mechanism of Ca2(+) mobilization during the differentiation of BC3H1 muscle cells. - De Smedt, H (1991)
Ca2+ sequestration and release in BC3H1 muscle cells is strongly dependent on the stage of differentiation. In proliferating cells, more than 90% of the sequestered Ca2+ was Ins(1,4,5)P3-sensitive and 25% was caffeine-sensitive. In differentiated cells, the Ca2+ accumulation was 5-fold higher and was InsP3-insensitive, but about 60% of the sequestered Ca2+ was caffeine-sensitive. These changes were reversible upon addition of growth stimuli. Similarly, by measuring the intracellular Ca2+ concentration in single intact BC3H1 cells, it was found that the number of histamine-responsive cells decreased and the number of caffeine-responsive cells increased during muscle cell differentiation. These data indicate that the development of the muscle phenotype in BC3H1 myoblasts induces a major rearrangement of the mechanisms for Ca2+ mobilization.